The Medievals on Aristotle's Doctrine of Substance - Gili, Luca (Recherches de théologie et philosophie médiévales, 2013)
Critical study ofThe Medieval Reception of Book Zeta of Aristotle’sG. GALLUZZO, Aristotle’s Ontology and the Middle Ages: The Tradition of Metaphysics. Book Zeta(I) Volume 1: Expositio in duodecim libros Metaphysicae Aristotelis Met., , Leiden/Boston, Brill, 2013, 774 pp.(II) Volume 2: PAULI VENETI , liber VII, Leiden/Boston, Brill, 2013, 609 pp.\n4207 \n4207